2020
DOI: 10.1177/1060028020949137
|View full text |Cite
|
Sign up to set email alerts
|

Phenobarbital Monotherapy for the Management of Alcohol Withdrawal Syndrome in Surgical-Trauma Patients

Abstract: Background Benzodiazepine is first-line therapy for alcohol withdrawal syndrome (AWS), and phenobarbital is an alternative therapy. However, its use has not been well validated in the surgical-trauma patient population. Objective To describe the use of fixed-dose phenobarbital monotherapy for the management of patients at risk for AWS in the surgical-trauma intensive care unit. Methods Surgical-trauma critically ill patients who received phenobarbital monotherapy, loading dose followed by a taper regimen, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 48 publications
0
46
0
Order By: Relevance
“…The baseline characteristics of the included studies are summarized in Table 1. A total of nine studies were included: one retrospective case series with more than 11 participants and including original data [10], seven retrospective studies [11][12][13][14][15][16][17], and one abstract with data relevant to the study design [18]. The sample sizes of the included studies ranged from 31 to 135 individuals.…”
Section: Search Resultsmentioning
confidence: 99%
“…The baseline characteristics of the included studies are summarized in Table 1. A total of nine studies were included: one retrospective case series with more than 11 participants and including original data [10], seven retrospective studies [11][12][13][14][15][16][17], and one abstract with data relevant to the study design [18]. The sample sizes of the included studies ranged from 31 to 135 individuals.…”
Section: Search Resultsmentioning
confidence: 99%
“… 18 Those patients with recent alcohol use (within 2 weeks of admission) with either a BAL of 0.1 g/dL or higher, elevated MCV (>90 fL), or elevated ALT to AST ratio greater than or equal to 1.5:1 are considered high risk as well. 22 23 Screening tools as described in previous sections can be used to identify patients who can benefit from empiric alcohol withdrawal prophylaxis as well. Current best practice is for patients deemed high risk to receive empiric prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Patients who may be at higher risk for hemodynamic changes include those with hepatic dysfunction, liver cirrhosis, traumatic brain injury, and recent opioid, sedative, or benzodiazepine administration. 22 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in emergency department settings suggest that phenobarbital used as a monotherapy improved the control of withdrawal and resulted in an equal or reduced need for inpatient and/or ICU admission compared with use of benzodiazepines ( 54 , 240 , 251 ). In the surgical–trauma ICU setting, phenobarbital-based protocols appear to be effective in preventing withdrawal-related complications, including delirium and clinically significant respiratory depression ( 252 , 253 ). One study in patients with trauma reported statistically significant decreases in the rates of progression to SAWS and medication adverse effects with phenobarbital compared to a fixed-dose benzodiazepine protocol ( 252 ).…”
Section: Section 3: Establishing Best Practices To Improve Clinical Outcomes (T 3 Research)mentioning
confidence: 99%